Influence of waste concrete aggregates on the performance and durability of OPC concrete / Ahmad Ruslan Mohd Ridzuan, Azmi Ibrahim and Abdul Manaff Mohd Ismail - Mohd Ridzuan, Ahmad Ruslan; Ibrahim, Azmi; Mohd Ismail, Abdul Manaff (Institute of Research, Development and Commercialisation (IRDC), 2005)
The effects of using crushed waste concrete as course aggregates upon compressive strength and carbonation were investigated. Waste concrete cubes, which had been tested for compressive strength in compliance with construction specification, were crushed and utilized as coarse recycled aggregates in new concrete. It is important to mention that, in order to simulate the real life conditions, waste concrete with very minimal information about its originality was used in its natural moisture condition. Tests on the aggregates showed that the recycled concrete aggregates have lower specific gravity and bulk density but have higher water absorption capacity than the natural aggregates. The resistance to mechanical actions such as impact and crushing for recycled concrete aggregates is also lower. Concrete mixes with design strength of 30 N/mm2, 35 N/mm2 and 40 N/mm2 were prepared using this recycled aggregates as coarse aggregates and tested. From the strength point of view the recycled aggregate concrete compared well with natural aggregate concrete. Therefore, it could be considered for various potential applications. With respect to resistance to carbonation the recycled aggregate concrete shows comparable performance.